2012 19th International Packet Video Workshop (PV) 2012
DOI: 10.1109/pv.2012.6229737
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of AL-FEC for RTP-based streaming video traffic to residential users

Abstract: Abstract-Real-time applications used by residential customers, such as streaming video and IPTV, are sensitive to packet losses, whether due to IP-layer congestion, or link-layer problems such as bit errors induced by impulse noise. To achieve acceptable user experience for these applications, numerous applicationlayer forward error correction (AL-FEC) schemes have been proposed. We evaluate some of the FEC schemes developed as part of the OpenFEC project, using packet loss traces of IPTVlike traffic measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…As part of the OpenFEC project, [43] examined the same codes as in [16] but with measured error traces from ADSL links rather than the random drops of [16]. These results confirmed those of [16] for random losses but showed that even at loss rates below 10% and with a code rate of 2/3, when error bursts occurred not all packets could be recovered.…”
Section: Related Workmentioning
confidence: 77%
“…As part of the OpenFEC project, [43] examined the same codes as in [16] but with measured error traces from ADSL links rather than the random drops of [16]. These results confirmed those of [16] for random losses but showed that even at loss rates below 10% and with a code rate of 2/3, when error bursts occurred not all packets could be recovered.…”
Section: Related Workmentioning
confidence: 77%
“…As part of the OpenFEC project, [30] examined the same codes as in [15] but with measured error traces from ADSL links rather than the random drops of [15]. These results confirmed those of [15] for random losses but showed that even at loss rates below 10% and with a code rate of 2/3, when error bursts occurred not all packets could be recovered.…”
Section: Related Workmentioning
confidence: 77%
“…α [2] α [2] + α [3] α [3] + α [4] + α [5] α [3] α [3] α [4] + α [5] α [5] + α [6] + α [7] α [5] α [4] α [5] + α [6] α [6] + α [7] + α [8] α [6] …”
Section: Now Consider the Sub-matrix Formed From Rowsunclassified